PSYCHOMETRIC STUDY OF THE SOCIAL SUPPORT SATISFACTION SCALE IN PEOPLE WITH PULMONARY TUBERCULOSIS - Silva, Maria Isabel Pereira da; Araújo, Beatriz Rodrigues; Amado, João Manuel da Costa (Cogitare Enfermagem, 2022)
Objective: to evaluate the psychometric properties of the Satisfaction with Social Support Scale in people with pulmonary tuberculosis. Method: methodological study developed in two stages: content validation of the items; and assessment of the psychometric properties of the Scale. Data were collected between October 2020 and January 2021 in a sample of 204 individuals with pulmonary tuberculosis in Pulmonary Diagnostic Centers in Northern Portugal. Results: The validated scale has a-Cronbach’s coefficient of 0.91, keeping the 15 items. There was a different distribution of items within the subscales, designated as: "Satisfaction with family" (a-Cronbach=0.94) now includes seven items; "Satisfaction with friends" a-Cronbach =0.85) includes only four items; "Social activities" (a-Cronbach=0.86) and "Intimacy" (a-Cronbach =0.77) go from three and four items of the original scale to two items each. Conclusion: the version of the Satisfaction with Social Support Scale can be a resource for planning nursing care for people with pulmonary tuberculosis.